1989
DOI: 10.1007/bf00001609
|View full text |Cite
|
Sign up to set email alerts
|

Gonopodial morphogenesis in female mosquitofish,Gambusia affinis affinis, masculinized by exposure to degradation products from plant sterols

Abstract: SynopsisFemale mosquitofish, Gambusia affinis affinis, were masculinized by exposure to degradation products (presumably steroids) of the plant sterol, stigmastanol. Masculinization was indicated by the induction of a male-like gonopodium in each specimen. The morphogenetic stages of gonopodial development are discussed as are the anatomical specializations produced in the mature gonopodial tip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 10 publications
0
48
0
Order By: Relevance
“…Microbial degradation of phytosterols (e.g., β-sitosterol and stigmastanol) commonly found in paper mill effluent has induced masculinized anal fin morphology in laboratory exposures (49,58). Other components of paper mill effluent include lignans and isoflavonoids (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial degradation of phytosterols (e.g., β-sitosterol and stigmastanol) commonly found in paper mill effluent has induced masculinized anal fin morphology in laboratory exposures (49,58). Other components of paper mill effluent include lignans and isoflavonoids (59).…”
Section: Discussionmentioning
confidence: 99%
“…Gonopodial development is androgen dependent and can be induced in females exposed exogenously to androgens (47,48). It has been hypothesized that bacterial biotransformation of plant sterols in the effluent generates the androgens responsible for the observed masculinization of female mosquitofish exposed to paper mill effluent (49). Recently, it was reported that androstenedione was present after a chemical characterization of the effluent from a paper mill plant in Florida (50).…”
mentioning
confidence: 99%
“…The increases of spiggin content in fish from ESC and RHO suggested that these fish were exposed to androgenic compounds. Surface water contamination by this class of endocrine disrupters is very little documented (Blankvoort et al, 2005;Soto et al, 2004) with the exception of pulp mill effluents that have an well-known masculinising effect (Cody and Bortone, 1997;Denton et al, 1985;Howell and Denton, 1989). Recently, Blankvoort et al (2005) reported contamination of European rivers by many androgens including testosterone and its metabolites, 17α-methyltestosterone or trenbolone, that were probably released in aquatic ecosystems by sewage treatment plants and industrial activities, and that could induce spiggin in female sticklebacks.…”
Section: Individual Effects In Contaminated Sitesmentioning
confidence: 99%
“…Phytosterols can be microbially transformed into C l9 steroids [21,22], and microbial removal of the aliphatic side chain of ß-sitosterol and stigmasterol transforms them into androstandienedione and androstenedione, respectively. It should be noted that in the effluent studied here, cholesterol is frequently found in similar quantities to phytosterols and thus is also a potential precursor to steroidal compounds as weil.…”
Section: In Vitra Goldfish Experimentsmentioning
confidence: 99%